A Statıstıcal Evaluatıon Of The Rıcketts Shortrange Fore Castıng Method From A Longıtudınal Sample - Dilek Erdem; Erhan Özdiler; Melike Uysal; Banu Erdoğan; Arzu Okul (Galenos Yayinevi, 1992)
This study was carried out on longitudinal lateral cephalometric and handwrist radiographs obtained from 40 individuals. Lateral cephalometric radiographs of the individuals which were taken during the S-stage (initial stage of puberty) and during the MP3u stage were chosen for the study. Direction of mandibular growth rotation was determined by superimposition of S and MP3u stage lateral cephalometric radiograps by Björk's structural method. On the S-stage lateral caphalogram prediction tracings of maxilla and mandible were made according to Ricketts Short-range forecasting method by taking into account the determined direction of mandibular rotation. Similarity between predicted values and real values at the end of the study period (MP3u Stage) was evaluated statistically for each measurement.